A review of the promises and constraints of breeding silver birch (Betula pendula Roth) in Finland - Koski, Veikko; Rousi, Matti (Forestry: An International Journal of Forest Research, 2005)
In comparison to the breeding of boreal conifers, silver birch ( Betula pendula Roth) has several advantages from the biological point of view. Flowering at an early age allows faster succession of generations, which together with rapid juvenile development can shorten the breeding cycle. Occurrence of natural polyploidy, inter-specific hybridization and the ability to propagate asexually offer optional breeding methods besides conventional recurrent selection. On the other hand, environmental factors have a strong impact on the performance of silver birch. Even though silver birch is ecologically a strong pioneer species, plantations in boreal forests often suffer from being eaten by mammalian herbivores, such as moose ( Alces alces ) and voles ( Microtus spp.). A large number of insect species attack silver birch, but except for cambium miner ( Phytobia betulae ) they are rarely economically important. Silver birch is also susceptible to some fungal pathogens. Resistance breeding is difficult because of the multitude of pests and diseases. The main stream of breeding was started with phenotypic selection in superior autochthonous stands followed by progeny testing and establishment of plastic-covered seed orchards. Considerable genetic gain has been achieved, even though more moderate than the most optimistic expectations of the early years. The utilization of advanced methods, such as gene transfers and micropropagation, is restricted because of public opinion and the stringent requirements set by the European Union directives and the Organization for Economic Co-operation and Development scheme on the marketing of forest reproductive material. The conspicuous oscillation of the interest and demand for birch wood by forest industries causes problems for long-term planning of breeding. However, the objective of improving silver birch using traditional methods is supported by public opinion. To successfully breed silver birch, close collaboration is recommended between the disciplines of genetics, silviculture ...